Training load within a soccer microcycle week - a systematic review - Silva, H.; Nakamura, F. Y.; Castellano, J.; Marcelino, R. (Strength and Conditioning Journal, 2023)
Quantifying training load is important to ensure that athletes correctly respond to training prescription and reduce injury risk. Training load can be divided into internal training load, the response of an individual to the training demand, and external training load, the physical "work" of the players. We aimed to analyze training load during a training week (microcycle) in soccer players. Systematic searches of 3 electronic databases (PubMed, SPORTDiscus, and Web of Science) were conducted, and Preferred Reporting Items for Systematic Review and Meta-analysis guidelines were followed. From 1,718 studies initially found, 16 were selected after screening. Descriptive and Z-score analyses were performed for each variable (acceleration and deceleration [DEC], average speed, high-speed running, sprint, total distance, player load, percentage of maximal heart rate, and rating of perceived exertion [RPE]). A sample of this review was 317 male soccer players aged 16.4-27.6 years, competing in elite, professional, and youth levels. Three days prior to match day was the most demanding session of the week, except for DEC, average speed, and player load demands. The day prior to match day was the least demanding session, except for sprint and RPE. In conclusion, midweek sessions can be chosen to apply higher training loads, whereas training sessions immediately before and after the match can be used to taper or recover.